CHALLENGES AND OPPORTUNITIES IN IMPLEMENTING FINANCIAL LITERACY PROGRAMS IN VIRUDHUNAGAR'S RURAL COMMUNITIES - Mathan, S. Jacob; Sunderaraj, R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The most vulnerable sections of society are often overlooked by formal financial institutions, driven by the pursuit of profit or the complexities involved in providing capital to these groups. Encouraging financially excluded individuals to engage with the formal financial system, promoting financial literacy, and strengthening credit delivery mechanisms are some of the significant challenges in achieving financial inclusion. An economy's growth is closely tied to how its citizens manage their finances, with the importance of personal savings being equally critical. Financial exclusion occurs when financial services are inaccessible to low-income and marginalized groups. In contrast, financial inclusion—or inclusive financing—refers to the provision of affordable financial services to these underserved populations. Financial inclusion aims to ensure that everyone, regardless of income level, has access to essential financial services. The primary goal of this public policy is to promote universal access to banking and payment services for all. Financial inclusion involves providing low-income and vulnerable populations with timely and affordable financial services when needed. To achieve this, nations must take proactive steps and implement necessary reforms to ensure that the most disadvantaged members of society are not left behind. In India, both the government and the Reserve Bank have historically played pivotal roles in developing banks and other financial infrastructure to enhance financial inclusion and provide high-quality financial products to those currently excluded from the system.